Monetary policy rules and reaction function in the Central Banks of the USA, Japan and European Union - Gollo, Romário de Souza; Triches, Divanildo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
This paper investigates the function of reaction of monetary policy following the approach of the Taylor Rule to evaluate the performance of this policy, lead for the Federal Reserve (FED), for the Bank of Japan (BOJ) and for European Central Bank (ECB), during the period selected for the research. It was considered for the analysis, as much for the FED how much for the BOJ, the period of January 1990 until June 2008; whereas for the ECB, in virtue of the constitution of the Euro Area, the analysis encloses January 1998 until June 2008. The estimates are made through the application of the Method of the Generalized Moments, of the Method of the Ordinary Least Squared and the Model of Autoregressive Conditional Heterocedasticity, whose results suggest that the Central banks of the U.S.A., the Japan and the Euro Area takes account its monetary policy decisions in the weighed deviation of the expectations of inflation, the output gap and the exchange rate. Moreover, a function of reaction of monetary policy for the Japanese economy shows that the objective real interest rate is adjusted in order to stabilize the inflation mainly. A function of reaction of monetary policy for the U.S.A. and the Euro area points out the target interest rate is set to accommodate the changes in the inflation and also, but with minor intensity, the output gap